An assessment of the competitiveness level of the human resources in science and technology (HRST) of the Department of Science and Technology - Vasquez, Maria Teresa M.; Posadas, Roger D. (Quezon City University of the Philippines Diliman, 2010)
The economic landscape of the future is characterized by growing risks and uncertainty. Take for example the financial crisis that only started in the United States and the United Kingdom and yet continued to spill over its effects to other economies including the developing countries. Many countries are now experiencing liquidity shortages, slumping demand for export products, falling commodity prices and significant reductions in foreign investments and remittances, among other things. In today's difficult economic environment, nations that have put in place long-term competitiveness fundamentals remain resilient to weather the storm. Studies on competitiveness of nations are extensively being conducted by two prominent organizations : the World Economic Forum (WEF) and the Institute of Management Development (IMD). The former publishes the annual Global Competitiveness Report while the latter the annual World Competitiveness Yearbook. Competitiveness is defined by the WEF as the set of institutions, policies, and factors that determine the level of productivity of a country. Accordingly, competitive economies tend to be able to produce higher levels of income for their citizens. On the other hand, the IMD views competitiveness as "How nations and businesses are managing the totality of their competencies to achieve greater prosperity". The term "Human resources for science and technology" (HRST) encompasses all personnel engaged in scientific and technological activities. HRST designates a category of highly trained and qualified personnel needed by any country that wishes to conduct scientific and technological activities (S&T). HRST is defined in terms of either qualifications or current occupation. In the former, the appropriate classification is the International Standard Classification of Education (ISCED) fifth, sixth, seventh classes; in the latter, it is the International Standard Classification of Occupations (ISCO) second and third classes (Chou, et al., 2008). The Organization for Economic Cooperation and Development (OECD) classifies research and development (R&D) personnel as only a part of HRST. ISCO 21 defines scientists and engineers as physical, mathematical and engineering science professionals; or life science and health professionals (ISCO 22) . Several studies have been done in evaluating the status of science and technology in the country focusing on areas such as the management of technologies, technology transfer and commercialization, and innovation among other things. Unfortunately, most of these studies fail to take into account the HRST and their capacity to contribute to economic growth and competitiveness of the nation. Cororaton (1999) attributed the very low technological capability of the Philippines to the severe lack of R&D personnel in industry such that with low R&D manpower capable of R&D work, any R&D investments cannot turn into productive results as desired.
The main purpose of this study is to assess the level of competitiveness of the available human resources in science and technology of the agencies of the Department of Science and Technology involved in R&D. The variables used to determine the level of competitiveness include language skills, extent of research cooperation/collaboration, public expenditure on education, tertiary education, number of researchers in R&D, number of scientific journal articles, and number of patents granted. On the demographic profile of the DOST R&D personnel, the study revealed that the mean age of R&D personnel is 42.25 years indicating that majority are in their senior years. There is an almost fifty-fifty male-female ratio among the researchers. Sixty-three percent of the DOST R&D personnel have a Bachelor's degree only while only 22.7 percent have a Master's degree as their highest degree. Results also showed that only 6.1 percent of the respondents have obtained a doctoral degree. The largest group (17.3 percent) of R&D personnel comes from the age bracket between 51 and 60 years old, which is dominated by female personnel. Female R&D personnel largely account for those with only a Bachelor's degree or a Master's degrees as their highest degree, while the males dominate those who are undergraduates and those with doctoral degrees. Twenty-four percent of personnel with a Bachelor's degree comes from the age bracket between 21 and 30 years old. Masters degree holders are concentrated within the age-group between 41 and 50 years old, while the doctoral degree holders are mostly found within the age-group between 51 and 60 years old. As the DOST R&D personnel were taken to represent the population of human resources in S&T in the country, national data gathered from various sources were used to come up with an indicative level of competitiveness using a scale constructed for the purpose of this study. Results reveal that our country, when compared to its neighbors, ranks poorly in almost all of the variables believed to be a factor in evaluating the competitiveness of the human resources in science and technology, namely : research collaboration, public expenditure on education, number of researchers in R&D, number of scientific articles published, and number of patents granted. Results also indicate that the Philippines ranks high only in the areas of language skills and completion of tertiary education. In this study, correlations test reveals that research cooperation/collaboration has the strongest relationship with competitiveness (r=.953, p<.05). This result suggests that there is a need to focus on increasing the extent of research cooperation among government research institutions, universities and industries in the country to expand knowledge base and transfer and stimulate performance of R&D personnel. The DOST should be able to provide monetary support to push for cooperation among these entities, establish a clear, aggressive and sustainable system of cooperation by putting in place inter-institutional structures, research networks, research alliances and agreements and institutional arrangements for sharing resources and equipment.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Competition (Psychology).; Human Resources in Science and Technology (HRST).; Department of Science and Technology (DOST).